ChemInform Abstract: Triphenylphosphine‐Catalyzed, Novel, One‐Pot, Multicomponent Synthesis of Functionalized β‐Acetamido Carbonyls. Issue 44 (4th November 2014) - Singh, Shyam Babu; Verma, Pankaj Kumar; Tiwari, Kamleshwar; Singh, Mandavi; Ankit, Preyas; Fatma, Shahin; Singh, Jagdamba; Tiwari, Kamla Prasad
Abstract The process is remarkably simple, environmentally benign, and uses Lewis base for the first time in such type of reaction.